Designing a Procedural Texts e-Book Using Local Wisdom of Tangerang City Foods - Destiani Rahmawati; Yudi Juniardi; Hidayatullah Hidayatullah (Jurnal Pendidikan Indonesia Gemilang, 2025)
This study aimed to identify suitable learning media for teaching English using procedural text concepts. The research employed an R D using ADDIE development model. From the review, the researcher designed an e-book learning media incorporating local wisdom, specifically focusing on Tangerang’s culinary heritage. This media was developed using the Contextual Teaching and Learning (CTL) approach to enhance the effectiveness of the learning process. The ADDIE model was applied as a systematic and procedural framework to guide the development of the learning media. The findings suggest that integrating local cultural elements into digital learning tools can improve student engagement and comprehension. The study concludes that e-books based on local wisdom, designed through a structured development model, offer a promising solution for modern English learning. Overall, this research highlights the potential of culturally relevant, technology-based media to support more meaningful and accessible education.